In vitro proliferative activity of 6-substituted uracil derivatives - Stanislav A. Grabovskiy; Natalia N. Kabal'nova; Nadezhda M. Andriayshina; Vladislav I. Egorov; Lenar R. Valiullin; Alexey A. Nabatov; Ivan S. Raginov; Yurii I. Murinov (GarVal Editorial Ltda., 2021)
Context: Previously, we investigated the relationship between the nature of the substituent at the 5-position of the uracil ring and the action of the corresponding uracil derivatives on immortalized lung cells. In the present study, we analyzed the impact of some 6-substituted uracil-derivatives on the regeneration potential of the lung cells (LC). Aims: To evaluate uracil derivatives capable of stimulating lung cell proliferation to create drugs that accelerate lung regeneration. Methods: The level of cell proliferation, maximum tolerated dose, and toxic effect of 6-substituted uracil derivatives (9 compounds) were studied on the immortalized lung epithelial cells and compared with the known drug 6-methyluracil. Results: The maximum tolerated dose of compounds for the LC line depends on the chemical structure of the compounds. The highest level of cell proliferation and tolerated was demonstrated when was used 3-methyl-6-cyclopropyluracil and 1-butyl-6-methyluracil. Conclusions: 3-methyl-6-cyclopropyluracil and 1-butyl-6-methyluracil exhibit a high proliferative activity in vitro so they could be recommended for additional studies of regenerative activity in vivo.